The Mediate Effect Of Sharia Compliance on The Performance of Islamic Banking in Indonesia - Usdeldi Usdeldi; M. Ridlwan Nasir; Muhamad Ahsan (Jurnal Keuangan dan Perbankan, 2022)
This study aimed to prove whether Sharia Compliance (SC) mediates the influence of Good Corporate Governance (GCG), Sharia Supervisory Board (SSB), and Corporate Social Responsibility (CSR) on financial performance and maqashid sharia performance in Islamic Commercial Banks (ICBs) in Indonesia. A regression analytical method was employed based on Structural Equation Modeling with panel data in the annual report published by ICBs in Indonesia for the period 2014-2019. The results proved that SC mediated GCG and CSR on maqashid sharia performance positively while negatively mediated them on financial performance. At the same time, it did not mediate SSB on both financial performance and maqashid sharia performance. Based on these findings, policymakers should launch regulations on the disclosure of the dimensions GCG, SSB, CSR, and SC in the annual reports of ICBs. In practical implementation, ICBs should improve GCG, CSR, and SC as the performance of Islamic banking-supporting dimensions, and, evaluate SSB as the non-supporting one